A representação do feminino nas poesias de Francisca Júlia (1871- 1920) - Borges, Jaqueline Ferreira (2018)
This work aims to consider the female subversive in some poems by Francisca Júlia, a São Paulo writer who published four literary works, being Mármores (1895), Livro da Infância (1899), Esphinges (1903) and, finally, in 1920, Alma Infantil. The poet was one of the pioneers of female insertion in literature, along with other names, started the authorship and freedom of women in writing. She faced the misogyny that invaded the nineteenth-century literature, but it reached space, recognition and admiration for important names in the intellectual scene of that period, but it became forgotten, requiring greater visibility in current scientific studies. In this sense, supported by Spivak (2010), the justification of our research is found, with the purpose of giving voice to the subordinate and creating means for him to be heard. The writer Francisca Júlia, who requires space, dealt with controversial themes, evidenced the feminine in her poems, presenting the mystical scene and the classical culture. We find imposing figures, impassive and sensuous, feminine that will be analyzed in this work. For the theoretical basis, we rely on authors and authors who present a critical study about the poet, such as Ramos (1961) and Camargos (2007). To reflect on the representation of the feminine, we use Beauvoir (2016), Bourdieu (2002) and Priore (2010). In order to deal with the condition of nineteenth-century women, their different dimensions and their insertion in writing, we rely on Duarte (2016) and Muzart (2004), among other theorists, who gave us subsidies to reflect the conditions of the nineteenth- protagonist, in the patriarchal universe of the nineteenth century.